Educadores universitários do Programa Escola da Família: uma reflexão sobre relatos de experiências e indicadores de evasão (2003-2011) - Silva, Edimicio Flaudisio (2013)
The Scholarship Program University (PBU) part of the Family School Program (AEP) from the Department of Education of the State of São Paulo presented the past eight years (2003- 2011), high dropout rates. The present study aimed to examine the difficulties of these fellows in the context in which it was conceived and in the run. Used as indicators of the sources of the PEF management system, external evaluations of SEADE and UNESP, legislation, studies of public policies for Scholarship Program for higher education in Brazil and the oral reports of dropouts and fellows who worked weekends in the Program. The regions chosen for interviews in the State of São Paulo were the regional representation: the capital (Board of Education - East 3), the greater São Paulo (Board of Education-Region Carapicuíba) and inside (Board of Education Region Fernandópolis). For the analysis procedures we perform and document the data collected during the interviews, we used the methodological indications of Bacellar (2005) and Toutier Bonazzi (2000), from a previously elaborated. The category experience Thompson (1981), substantiated the conduct of research, especially in regard to understanding the itinerary of subjects as participants of these programs. Thus, the results of the experiments reported and all documents examined, it was found that internal factors, external institutions, individual characteristics and conditions of the scholarship, are barriers that can hinder continuity in PBU. Seeking discuss and present the various contradictions in the documentation governing its operation, we found that dropout rates of PBU outweigh those of Brazil and the State of São Paulo. The research sought to examine the linkages between activities in schools by scholars and their academic studies in HEIs. With reports of experiences, we discover different types of silence or inadequacy of this Program